Comparing Nias Cultural Beliefs and Cyril’s Theological Anthropology - Hendi; Lawolo, Aprianus; Sugianto; Elifas, Nadia Bimantoro; Indradjaja, Daniel (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2026)
This study seeks to enhance the quality of discipleship in churches based in Nias by contrasting Cyril of Jerusalem's theological anthropology with Nias' cultural conceptions of body and soul, with a particular emphasis on noso. Using a qualitative literature review, thematic content analysis, and comparative methods from theology, religious studies, anthropology, and missiology, the study identified both similarities and differences between Nias’ culture and Cyril’s theological anthropology. Cyril's framework, characterized by its clarity and bipartite structure, places significant emphasis on the concept of the imago Dei, bodily resurrection, and an eternal soul. In contrast, Nias tradition teaches a complex anthropology comprising multiple elements and a cyclical eschatology. The study concluded that Cyril's theological anthropology exerts a positive influence on Nias Christian discipleship by fortifying Nias spiritual intuitions and providing a more lucid theological framework. Furthermore, it serves as a conduit between Christian theology and Nias traditions, offering a foundation for more effective and contextually sensitive discipleship. This integration of traditional values with universal Christian teachings results in a more profound and culturally relevant faith, and ultimately guides practical discipleship strategies in Nias, thereby promoting both qualitative and quantitative church growth.